On the debate of original drug versus generic drug - (:unkn) unknown (KURE ILETISIM GRUBU A S, 2009)
The original drugs are protected by the world's most powerful patent protection laws for a certain period of time and sonar equivalent (generic) drugs may be manifactured at the end of the patent protection period. Generic drugs are not only pharmaceutical drugs equivalent to the original generic drugs, but they should also be bioequivalent. Countries who want to reduce health costs, may provide significant savings by using generics. Generic drugs are usually 20-80% cheaper than the originals. It has been announced that TL 3 billion 879 million was saved from the total health expenditures between the years 2004-2008 with the use of generics. Since it is planned that the general health insurance system will eventuate and therefore the health system will cover almost all the population, the use of generic drugs-which are much cheaper than the originals- will provide benefit in terms saving from the public health expenditures will provide advantages in terms of savings. According to the impression we have obtained from clinical practice and research data, we believe that the generics which are manifactured under control and cover the necessary rules, are as effective as the originals. On the other hand, limited clinical observations with some generics may justify the doubts of the clinicians. We believe that these doubts can be eliminated by the strict control conducted by the regulators in the light of feedback obtained from the clinicians.
Keywords: Original drug; generic drug; bioavailability; bioequivalence